A single non-synonymous NCOA5 variation in type 2 diabetic patients with hepatocellular carcinoma impairs the function of NCOA5 in cell cycle regulation. (10th April 2017) - Liu, Xinhui; Liu, Feiye; Gao, Shenglan; Reske, Jake; Li, Aimin; Wu, Chin-Lee; Yang, Chengfeng; Chen, Fengsheng; Luo, Rongcheng; Xiao, Hua
Abstract: Type 2 Diabetes (T2D) is a risk factor for hepatocellular carcinoma (HCC). We have previously described that haploinsufficiency of nuclear receptor coactivator 5 (NCOA5) is a genetic defect linking glucose intolerance to HCC. Here we report identification and characterization of a single nucleotide variation (T445A) in NCOA5, causing an amino acid Thr to Ala substitution, in adjacent non-tumorous liver tissues derived from patients with concurrent HCC and T2D. By using Tet-On inducible expression cells, we show that ectopic expression of NCOA5wt suppressed proliferation of HCC cells via induction of G2/M arrest, while ectopic expression of NCOA5T445A had a significantly lesser effect compared to ectopic expression of NCOA5wt. Furthermore, ectopic expression of NCOA5wt increased the occurrence of DNA damage and cell senescence, whereas expression of NCOA5T445A partly lost this activity. Xenograft tumor model analysis demonstrated that ectopic NCOA5wt expression reduced HCC tumor growth and the T445A variation impairs its tumor growth inhibitory function. Collectively, our data show that the T445A variation impairs the ability of NCOA5 to inhibit growth of HCC, suggesting that this variation may have potential to increase susceptibility to HCC comorbid with T2D. Highlights: Identification of a T445A variation in NCOA5 gene from patients with both HCC and T2D. NCOA5 inhibits proliferation of HCC cells via promoting G2/M phase cell cycle arrest. The T445A impairs the ability of NCOA5 to inhibit growth of xenograft tumors.